ICE FLOW BEHAVIOR AT DYE 3,GREENLAND - ショウジ, ヒトシ /; SHOJI, Hitoshi; LANGWAY, Chester C. (National Institute of Polar Research, 1990)
P(論文) To understand the flow behavior of large polar ice masses, mechanical property studies have been conducted on deep ice core samples obtained at Dye 3,Greenland during the GISP field operations from 1979 to 1981. A strain rate enhancement factor profile obtained by making uniaxial compression tests shows (1) much higher enhancement factor values for Wisconsin age ice compared with Holocene ice and (2) characteristic changes in the enhancement factor value for the Wisconsin ice depth zone. These results were incorporated to calculate both horizontal and vertical flow velocity profiles of ice which are in good agreement with the results of borehole tilting measurements and computer models of flow dynamics. The finding of depth changes in enhancement factor value leads to a consideration of possible formation of boudinage structure. Further studies are required to fully understand the differential flow behavior of large ice sheets. departmental bulletin paper